Resolving the dust-to-metals ratio and CO-to-H2 conversion factor in the nearby universe - Chiang, I-Da; Sandstrom, Karin M.; Chastenet, Jérémy; Herrera, Cinthya N.; Koch, Eric W.; Kreckel, Kathryn; Leroy, Adam K.; Pety, Jérôme; Schruba, Andreas; Utomo, Dyas; Williams, Thomas (The astrophysical journal, 2021)
We investigate the relationship between the dust-to-metals ratio (D/M) and the local interstellar medium environment at ∼2 kpc resolution in five nearby galaxies: IC 342, M31, M33, M101, and NGC 628. A modified blackbody model with a broken power-law emissivity is used to model the dust emission from 100 to 500 μm observed by Herschel. We utilize the metallicity gradient derived from auroral line measurements in H i regions whenever possible. Both archival and new CO rotational line and H i 21 cm maps are adopted to calculate gas surface density, including new wide-field CO and H i maps for IC 342 from IRAM and the VLA, respectively. We experiment with several prescriptions of the CO-to-H2 conversion factor and compare the resulting D/M-metallicity and D/M-density correlations, both of which are expected to be nonnegative from depletion studies. The D/M is sensitive to the choice of the conversion factor. The conversion factor prescriptions based on metallicity only yield too much molecular gas in the center of IC 342 to obtain the expected correlations. Among the prescriptions tested, the one that yields the expected correlations depends on both metallicity and surface density. The 1σ range of the derived D/M spans 0.40-0.58. Compared to chemical evolution models, our measurements suggest that the dust growth timescale is much shorter than the dust destruction timescale. The measured D/M is consistent with the D/M in galaxy-integrated studies derived from infrared dust emission. Meanwhile, the measured D/M is systematically higher than the D/M derived from absorption, which likely indicates a systematic offset between the two methods.
Im Titel ist "2" in CO-to-H2 tiefgestellt
Gesehen am 09.03.2021